Host and Pathway Engineering for Enhanced Lycopene Biosynthesis in Yarrowia lipolytica - Schwartz, Cory; Frogue, Keith; Misa, Joshua; Wheeldon, Ian (Frontiers in Microbiology, 2017)
Carotenoids are a class of molecules with commercial value as food and feed additives with nutraceutical properties. Shifting carotenoid synthesis from petrochemical-based precursors to bioproduction from sugars and other biorenewable carbon sources promises to improve process sustainability and economics. In this work, we engineered the oleaginous yeast Yarrowia lipolytica to produce the carotenoid lycopene. To enhance lycopene production, we tested a series of strategies to modify host cell physiology and metabolism, the most successful of which were mevalonate pathway overexpression and alleviating auxotrophies previously engineered into the PO1f strain of Y. lipolytica. The beneficial engineering strategies were combined into a single strain, which was then cultured in a 1-L bioreactor to produce 21.1 mg/g DCW. The optimized strain overexpressed a total of eight genes including two copies of HMG1, two copies of CrtI, and single copies of MVD1, EGR8, CrtB, and CrtE. Recovering leucine and uracil biosynthetic capacity also produced significant enhancement in lycopene titer. The successful engineering strategies characterized in this work represent a significant increase in understanding carotenoid biosynthesis in Y. lipolytica, not only increasing lycopene titer but also informing future studies on carotenoid biosynthesis.